Can ICT make small beautiful? Examining the role of ICT in affecting the credit behavior of SMEs in India - Ritika Jain; Shreya Biswas (Asian Development Bank Institute (ADBI), 2024)
The paper explores the relationship between ICT adoption and credit behavior for small and medium enterprises in India. We use the latest round of the World Bank Enterprise Survey for India, conducted in 2021, and employ an instrumental variable estimation technique to account for any potential endogeneity between ICT adoption and credit behavior. We find that better ICT usage enhances the likelihood of obtaining credit and the size of credit for these firms. Additionally, it increases the likelihood of applying for loans and loan approvals. We also examine the result for micro firms in India and find confirmation of our findings. On exploring further, we find evidence that reduced information asymmetry, better financial awareness, innovation, and enhanced productivity are possible channels that improve access to credit for small and medium firms. The study underscores the role of ICT in reducing the credit constraints of small and medium enterprises.
Keywords: D22; O14; H81; L86; 330; small and medium-sized enterprises; credit; information and communication technology